(untitled) (Research, Society and Development, 2022)
Auxiliary devices are resources that allow an additional support of the human body to the ground, and used by people with locomotion difficulties. The theme of this exploration raises a discussion about the technical aids that permeate the understanding of the barriers that the user faces in the development of a device so that the Canadian crutch can stand up, once it is not in use. It is also understood that this factor is directly associated with people with disabilities, given that a satisfactory life goes beyond coming and going or having access to places, as well as being emancipated in carrying out routine actions. The objective of the work was to develop a device to be incremented to the Canadian crutch, using the SolidWorks program to simulate its functionality. The proposal of the work is to add a tripod that, activated by a button, allows the crutches to stop standing up, avoiding the problem related to the fall of the object under study. To use the SolidWorks program, it was necessary to develop a sketch, that is, the design of the different parts that make up the device to be added to the Canadian crutch. The results showed the perfect functioning of the device via computational simulation, leaving a good expectation when applying this apparatus in the physical system.